Myricitrin Modulates NADPH Oxidase‐Dependent ROS Production to Inhibit Endotoxin‐Mediated Inflammation by Blocking the JAK/STAT1 and NOX2/p47 phox Pathways - Qi, Shimei; Feng, Zunyong; Li, Qiang; Qi, Zhilin; Zhang, Yao (Oxidative medicine and cellular longevity, 2017)
Myricitrin, a naturally occurring polyphenol hydroxy flavonoid, has been reported to possess anti‐inflammatory properties. However, the precise molecular mechanism of myricitrin’s effects on LPS‐induced inflammation is unclear. In the present study, myricitrin significantly alleviated acute lung injury in mice. Myricitrin also markedly suppressed the production of NO, TNF‐α, IL‐6, and MCP‐1 in RAW264.7 macrophage cells. The inhibition of NO was concomitant with a decrease in the protein and mRNA levels of iNOS. The phosphorylation of JAKs and STAT‐1 was abrogated by myricitrin. Furthermore, myricitrin inhibited the nuclear transfer and DNA binding activity of STAT1. The JAK‐specific inhibitor ruxolitinib simulated the anti‐inflammatory effect of myricitrin. However, myricitrin had no impact on the MAPK signalling pathway. Myricitrin attenuated the generation of intracellular ROS by inhibiting the assembly of components of the gp91 phox and p47 phox . Suppression of ROS generation using NAC or apocynin or by silencing gp91 phox and p47 phox all demonstrated that decreasing the level of ROS inhibited the LPS‐induced inflammatory response. Collectively, these results confirmed that myricitrin exhibited anti‐inflammatory activity by blocking the activation of JAKs and the downstream transcription factor STAT1, which may result from the downregulation of NOX2‐dependent ROS production mediated by myricitrin.